The struggle for National Identity: cultural and ethnic conflicts in Achebe’s Things Fall Apart and No Longer at Ease - Ferrara, Bernardo (ContraPonto, 2013)
By colonizing Nigeria in the early 1900s, the British ruled over a vast ethnically diverse population. Their presence set about cultural andpolitical changes which were decisive to determine Nigeria’s future. Inhis novels Things Fall Apart (1958) and No Longer at Ease (1960), Chinua Achebe, one of the greatest Nigerian writers, show us the struggle present in a colonized Nigeria. The main characters seem uneasy as they see themselves amidst fast pacing changes, and they seem unable to adapt to them. What is Nigeria? What does it mean to be Nigerian? With these questions in mind, this article points out and discusses the characters’ struggle for national identity throughout these novels, comparing and contrasting the period and society in which each character lives as well as their dismay.